2022
DOI: 10.1186/s12877-022-03377-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of visceral fat area with pre-frailty in Japanese community-dwelling older adults: a cross-sectional study

Abstract: Background Screening and intervention in pre-frailty can help prevent or delay frailty among older adults. Being overweight has shown associated with pre-frailty, and overweight is highly prevalent among community-dwelling older adults during COVID-19. However, the impact of visceral fat accumulation remains unclear. This study aimed to explore the association between visceral fat area and pre-frailty in community-dwelling older adults. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Glycoprotein acetyls are markers of in ammation and they may contribute to in ammaging, the low grade in ammation occurring during aging predisposing to many age-related diseases (Franceschi et al, 2014). A very recent study demonstrated that glycoprotein acetyls are positively associated with frailty index in older age (Bålsrud et al, 2024), however, no study has associated glycoprotein acetyls with EAA before. While our ndings are supported by the previous studies on in ammaging and frailty in older age, it also adds to the literature by demonstrating a direct link between glycoprotein acetyls and EAA, which is present already in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Glycoprotein acetyls are markers of in ammation and they may contribute to in ammaging, the low grade in ammation occurring during aging predisposing to many age-related diseases (Franceschi et al, 2014). A very recent study demonstrated that glycoprotein acetyls are positively associated with frailty index in older age (Bålsrud et al, 2024), however, no study has associated glycoprotein acetyls with EAA before. While our ndings are supported by the previous studies on in ammaging and frailty in older age, it also adds to the literature by demonstrating a direct link between glycoprotein acetyls and EAA, which is present already in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence, including our previous research [8,9], suggests that high adiposity, assessed by anthropometric measures such as body mass index (BMI) and waist circumference (WC) [10][11][12][13][14], as well as dualenergy X-ray absorptiometry (DXA)-derived measures such as fat mass index (FMI) and visceral adipose tissue (VAT) mass [14][15][16][17][18][19], is an important risk factor for pre-frailty and frailty. Given the rising obesity epidemic across all age groups [20], this is of major concern.…”
Section: Introductionmentioning
confidence: 99%